Flouting Maxims in The First Grader (2010) Movie - Rahayu Rahayu; Susilawati Susilawati (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
This study investigated about the flouting of Grice’s maxims in The First Grader movie. This study concerned on finding the types of flouting maxim that occur in the movie and examine the reasons why the characters of The First Grader movie flouted the Grice’s maxims in the dialogue. The present study employs descriptive qualitative research, by analyzing critically each conversation occurr in the movie. The data of the study were in the form of utterances that contained a flouting maxim. The context of conversation in the movie also took a part as the evidence if it is flouting maxims. Implicatures that caused by the speaker is also become the important element in investigated the reason why those maxim are flouted by considering the linguistic context, cultural context, and situational context. The results of the research showed from twenty five utterances that indicated flouting maxim, all types of maxim were flouted in the movie. They were maxim of quantity (18,5%), maxim of quality (22,2%) , maxim of relation (29,6%), and maxim of manner (29,6%). From the finding and analysis, the writers concluded that in several conditions the characters of the movie were flouting the maxims because of some reasons. The major reason that occur in the movie are to give sarcasm, to express angry, and to convince someone. Keywords: Cooperative Principle: Flouting maxim: Context of conversation: Implicatures, Movie;